EVIDENCE BASED CASE REPORT (EBCR) : PENGGUNAAN BIRTH BALL EFEKTIF DALAM MENGURANGI NYERI PERSALINAN KALA I (Jurnal Kesehatan Siliwangi, 2022)
Background: Labor pain is a physiological condition experienced in childbirth, labor pain can affect the physical and psychological conditions of childbirth. Handling pain in labor can be  pharmacologically using pharmacological or non-pharmacological in the form of the use of birth balls. Non-pharmacological pain reduction techniques have the best effect for a short time, are inexpensive, and have no side effects. The role of midwives reduces the severity of pain and anxiety in women during childbirth and creates a positive birth experience, this can be realized by using non-pharmacological methods. Purpose: to determine the effectiveness of birth balls on first stage labor pain. Method : The method used is a Evidence Based Case Report. using pubmed and science direct, and 2 RCT articles have been critically reviewed. Result :  The results of the search showed that the birth ball method was effective in reducing pain in the first stage of labor, with a decrease in the pain scale from the range of 75-100 mm to 45-74 mm after the intervention for 30 minutes. Conclusion: The use of a birth ball has been proven effective in reducing labor pain during the first active phase, the birth ball helps in positioning the mother's body optimally and has the effect of reducing pain when the uterus contracts.